2005
DOI: 10.1007/s00438-005-1149-2
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of the nematode resistance gene Mi-3 in Solanum peruvianum and construction of a S. lycopersicum DNA contig spanning the locus

Abstract: Currently, the only genetic resistance against root-knot nematodes in the cultivated tomato Solanum lycopersicum (Lycopersicon esculentum) is due to the gene Mi-1. Another resistance gene, Mi-3, identified in the related wild species Solanum peruvianum (Lycopersicon peruvianum) confers resistance to nematodes that are virulent on tomato lines that carry Mi-1, and is effective at temperatures at which Mi-1 is not effective (above 30 degrees C). Two S. peruvianum populations segregating for Mi-3 were used to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 37 publications
0
18
0
7
Order By: Relevance
“…UC research has been instrumental in identifying and evaluating genetic material resistant to a variety of soil pests and diseases, such as root knot nematodes (Kaloshian et al 1996;Yaghoobi et al 2005), Fusarium wilt (Scott et al 2012) and Armillaria (Baumgartner et al 2013). Recent field research evaluating experimental rootstocks for almond and stone fruit has found that some hybrids are markedly less sensitive to Prunus replant disease than others, which may result in less need for chemical controls ).…”
Section: Breedingmentioning
confidence: 99%
“…UC research has been instrumental in identifying and evaluating genetic material resistant to a variety of soil pests and diseases, such as root knot nematodes (Kaloshian et al 1996;Yaghoobi et al 2005), Fusarium wilt (Scott et al 2012) and Armillaria (Baumgartner et al 2013). Recent field research evaluating experimental rootstocks for almond and stone fruit has found that some hybrids are markedly less sensitive to Prunus replant disease than others, which may result in less need for chemical controls ).…”
Section: Breedingmentioning
confidence: 99%
“…Tomato is one of the top most crop species for which genetic markers are used in commercial breeding by last few years (Foolad 2007). Yaghoobi et al (2005) identified a tightly linked marker that is completely co-segregated with a single dominant gene Mi-3 resistant to RKN. It can be used to identify Mi-3 introgression in commercial tomato cultivars by either conventional breeding or cloning.…”
Section: Marker-assisted Breedingmentioning
confidence: 99%
“…S. peruvianum also showed strong resistance ( Table 1). The nematode resistance loci Mi-3 in S. peruvianum was mapped on chromosome 12 (Yaghoobi et al, 2005), but has not yet been cloned. We also found that S. pennellii showed weak resistance to root-knot nematode infection (Table 1).…”
Section: Resultsmentioning
confidence: 99%